(untitled) (Journal of Kathmandu Medical College, 2017)
Background: Need of second trimester abortion has been increasing because of the wide scale introduction of prenatal screening programs detecting women whose pregnancies are complicated by serious fetal abnormalities. Lack of accredited centers and skills required for mid trimester abortion have made this procedure inaccessible to rural population of Nepal. Objectives: This study was conducted to assess correlation of uterine size measured by clinical examination and that assessed by ultrasound, foetal foot length measurement post abortion, dose of misoprostol required and induction delivery interval in medical induction and dilatation and evacuation cases. Methods: This is a hospital based cross-sectional study conducted from April 2011 to July 2012. gestational age was assessed by clinical palpation and ultrasound in women undergoing mid trimester abortion. Standard protocol was followed for medical and surgical abortion. Fetal foot length was measured post abortion. Mean dose of misoprostol and induction abortion interval were noted. Results: Mean age of the patients in dilatation and evacuation group and medical induction group were similar 28 (SD= 6.2) and 27 (SD=7) respectively. The mean dose of misoprostol requiredwas 400 micrograms for dilatation and evacuation and 600 micrograms for medical induction. There was moderate degree of relationship between foot length measurement of the fetus and USG findings, high degree of positive relationship between size of the uterus and fetal foot length measurement. Conclusion: Clinical estimation of period of gestation by size of the uterus correlated well with ultrasonography findings and fetal foot length measurement post abortion. The mid trimester service can thereforebe provided in the centers where sophisticated appliances like ultrasonography is not available.